The effect of the finite size of ions and Debye layer overspill on the screened Coulomb interactions between charged flat plates. Issue 7 (22nd January 2020) - Paul, Arghyadeep; Mukherjee, Siddhartha; Dhar, Jayabrata; Ghosal, Sandip; Chakraborty, Suman
Abstract: Screened repulsion between uniformly charged plates with an intervening electrolyte is analyzed for strongly overlapped electrical double layers (EDL), accounting for the steric effect of ions and their expulsion from EDL edges into the surrounding solution. As a generalization of a study by Philipse et al. which does not account for these effects, an analytical expression is derived for the repulsion pressure in the limit of infinitely long plates with a zero‐field assumption, which agrees closely with the corresponding numerical solution at low inter‐plate separations. Our results show an augmented repulsive pressure for finite‐sized ions at strong EDL overlaps. For plates with a finite lateral size, we demonstrate a further extended domain of low inter‐plate gaps where the repulsion pressure increases with ion size due to a strong interplay between the steric interaction of ions and the EDL overspill phenomenon, considered earlier in a study by Ghosal & Sherwood limited to the linear Debye‐Hückel regime (which cannot account for the steric effect of ions). This investigation on a simple model should enhance our understanding of the interaction between charged particles in electrophoresis, nanoscale self‐assembly, active particles, and various other electrokinetic systems.